The Effectiveness of The Academic Writing Course on The Writing Techniques of English Language Education Students - Hardianti, Sitti; N.Sabata, Yusniati (Universitas Muhammadiyah Sorong, 2025)
This study examines the effectiveness of the Academic Writing course in enhancing the writing skills of third-semester university students. The research specifically investigates improvements in technical writing aspects such as punctuation, capitalization, grammar, vocabulary, and the construction of coherent and logically structured paragraphs. Employing a qualitative descriptive approach, data were collected through quisionnaire, analysis of students’ written assignments. The findings demonstrate that the Academic Writing course significantly contributes to the improvement of students’ writing proficiency, notably in accuracy and adherence to academic writing conventions. Students displayed increased awareness and consistent application of proper writing techniques, resulting in more structured and clear academic texts. The study recommends incorporating more interactive and context-based teaching strategies to further enhance student engagement and writing outcomes. These findings underscore the importance of Academic Writing courses as a foundational component in undergraduate curricula to prepare students for academic and professional success.